2018
DOI: 10.1038/s41598-018-27089-7
|View full text |Cite
|
Sign up to set email alerts
|

NCAM2 Fibronectin type-III domains form a rigid structure that binds and activates the Fibroblast Growth Factor Receptor

Abstract: NCAM1 and NCAM2 have ectodomains consisting of 5 Ig domains followed by 2 membrane-proximal FnIII domains. In this study we investigate and compare the structures and functions of these FnIII domains. The NCAM1 and -2 FnIII2 domains both contain a Walker A motif. In NCAM1 binding of ATP to this motif interferes with NCAM1 binding to FGFR. We obtained a structural model of the NCAM2 FnIII2 domain by NMR spectroscopy, and by titration with an ATP analogue we show that the NCAM2 Walker A motif does not bind ATP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The extracellular domain of NCAM2 has been shown to bind to Aβ oligomers ( 42 ). The FN2 domain of NCAM2 could also bind and activate FGFR1, inducing neurite outgrowth ( 78 ). It is therefore possible that the sNCAM2 acts as a dominant negative by binding to membrane-bound NCAM2-FL or other binding partners to NCAM2.…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular domain of NCAM2 has been shown to bind to Aβ oligomers ( 42 ). The FN2 domain of NCAM2 could also bind and activate FGFR1, inducing neurite outgrowth ( 78 ). It is therefore possible that the sNCAM2 acts as a dominant negative by binding to membrane-bound NCAM2-FL or other binding partners to NCAM2.…”
Section: Discussionmentioning
confidence: 99%
“…The TOMM6 gene has not been reported. NCAM2 is a close homolog of the neuronal cell adhesion molecule NCAM1 and stimulates neurite outgrowth through FGFR-dependent activation of the Ras/MAPK pathway (34,35). Several studies have reported that NCAM2 can be used as a new therapeutic target for cancer, especially prostate cancer and breast cancer (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance in the expression levels of LRP1 in fibroblasts of healing tissues may lead to unlimited expansion of contractile fibroblasts, thus causing or aggravating pulmonary fibrosis and participating in the pathogenesis of asthma (Schnieder et al, 2019). Neural cell adhesion molecule 2 (NCAM2) protein has been shown to reduce inflammation in Alzheimer's disease (Rasmussen et al, 2018). CNTN1, which is also a cell adhesion protein, can promote the invasion of prostate cancer cells, enhance Akt activation, and reduce the expression of epithelial cadherin in cancer cells (Yan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%